RANCANG BANGUN SISTEM INFORMASI SANTRI EL-BAYAN BERBASIS WEBSITE - alfiah, nurul (Jurnal Teknologi dan Bisnis, 2020)
Current technological developments play an important role in human life, especially in the world of education and Islamic boarding schools, because in such a short time and over such a wide distance information can be conveyed or received accurately and actually. At this time the El-Bayan Majenang Islamic Boarding School is still lacking in providing information to the wider community, namely only by using social media accounts. With the technology that is developing rapidly at this time, especially the internet, a website is designed at the El-Bayan Majenang Islamic Boarding School which is expected to help pesantren in facilitating the process of delivering information related to the scope of pesantren, especially to the general public.